Rhodium‐Catalyzed Asymmetric Hydrogenation of All‐Carbon Aromatic Rings - Ding, Yi‐Xuan; Zhu, Zhou‐Hao; Chen, Mu‐Wang; Yu, Chang‐Bin; Zhou, Yong‐Gui (Angewandte Chemie International Edition, 2022)
Compared with heteroarenes, homogeneous asymmetric hydrogenation of all‐carbon aromatic rings is a longstanding challenge in organic synthesis due to the strong aromaticity and difficult enantioselective control. Herein, we report the rhodium/diphosphine‐catalyzed asymmetric hydrogenation of all‐carbon aromatic rings, affording a series of axially chiral cyclic compounds with high enantioselectivity through desymmetrization or kinetic resolution. In addition, the central‐chiral cyclic compounds were also obtained by asymmetric hydrogenation of phenanthrenes bearing a directing group. The key to success is the introduction of chiral diphosphine ligands with steric hindrance and strong electron‐donating properties. The axially chiral monophosphine ligands could be obtained by simple conversion of the hydrogenation products bearing the phosphine atom. The first rhodium/diphosphine‐catalyzed asymmetric hydrogenation of all‐carbon aromatic rings, anthracenes and naphthalenes, was reported, affording the axially chiral biaryl compounds by desymmetrization or kinetic resolution. Meanwhile, central‐chiral cyclic compounds were also obtained by asymmetric hydrogenation of phenanthrenes. In addition, after simple conversion of the products, the axially chiral monophosphine ligands could be obtained.